2022
DOI: 10.3390/clinpract12040055
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Patients with Acute Coronary Syndromes Receiving Care from Public and Private Health Care Systems in Brazil

Abstract: (1) Background: Quality of life (QOL) is used as a health indicator to assess the effectiveness and impact of therapies in certain groups of patients. This study aimed to analyze the QOL of patients with acute coronary syndrome (ACS) who received medical treatment by a public or private health care system. (2) Methods: This observational, prospective, longitudinal study was carried out in four referral hospitals providing cardiology services in Sergipe, Brazil. QoL was evaluated using the Medical Outcomes Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The result showed that there was a significant difference in the HRQoL score for patients in BUTH (M = 98.31, SD = 14.58) and patients in FMCA (M = 84.38, SD 28.06); t (325.978) = -6.308, p = < .001.These results suggest that receiving care in different tertiary hospitals [either public or private] does have an effect on patients' health-related quality of life. The findings in this study suggest that prostate cancer patients receiving care in private tertiary hospitals have a better Health-Related Quality of Life (HRQoL) compared to prostate cancer patients receiving care in public tertiary hospitals; this validated the findings of DeCarvalho et al (2022), who conducted an observational, prospective, longitudinal study to examine the Quality of Life (QoL) among Acute Coronary Syndrome (ACS) patients who got professional medical care in either a public or privately owned health care facility. They found that the group of participants who received care from public/government health care facilities had lower quality of life scores compared to the group who received care from private health care facilities.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The result showed that there was a significant difference in the HRQoL score for patients in BUTH (M = 98.31, SD = 14.58) and patients in FMCA (M = 84.38, SD 28.06); t (325.978) = -6.308, p = < .001.These results suggest that receiving care in different tertiary hospitals [either public or private] does have an effect on patients' health-related quality of life. The findings in this study suggest that prostate cancer patients receiving care in private tertiary hospitals have a better Health-Related Quality of Life (HRQoL) compared to prostate cancer patients receiving care in public tertiary hospitals; this validated the findings of DeCarvalho et al (2022), who conducted an observational, prospective, longitudinal study to examine the Quality of Life (QoL) among Acute Coronary Syndrome (ACS) patients who got professional medical care in either a public or privately owned health care facility. They found that the group of participants who received care from public/government health care facilities had lower quality of life scores compared to the group who received care from private health care facilities.…”
supporting
confidence: 75%
“…It was observed among black men that having a source of social support was a prominent factor in increasing their healthrelated quality of life (Sauer et al, 2022). Similarly, an observational, prospective, longitudinal study was conducted by De Carvalho et al (2022) to examine the Quality of Life (QoL) among Acute Coronary Syndrome (ACS) patients who got professional medical care in either a publicor privately-owned health care facility; they found that the group of participants who received care from public/government health care facilities had lower quality of life scores for all the different domains of quality of life (functional capacity, physical aspects, pain, general health status, vitality, social condition, emotional profile, and health) than the group who receives care from private healthcare facilities. Furthermore, financial hardship among Latinos residing in USA (United States of America) was found to be associated with poorer Health-Related Quality of Life (HRQoL) in that population (Nedjat-Haiem et al, 2021), Latinos in the United States struggle financially and it is quite difficult for them to gain employment where health insurance coverage is part of job benefits (Cheney et al, 2018); similarly, this study was conducted to assess the HRQoL of Prostate cancer patients receiving care in both public and private tertiary hospitals in Nigeriaa region in sub-Saharan Africa, known for similar economic hardship and inadequate health insurance coverage within its population.…”
Section: Introduction Background To the Studymentioning
confidence: 99%
“…QOL is used as a health indicator to assess the effectiveness and impact of therapies in certain groups of patients [ 22 ]. In Clinics and Practice , de Carvalho Costa et al [ 23 ] aimed to analyze the QOL of patients with ACS who received medical treatment from a public or private health care system in an observational, prospective, longitudinal study carried out in Sergipe, Brazil. At 180 days after ACS, the public health care group had lower QoL scores for all domains (functional capacity, physical aspects, pain, general health status, vitality, social condition, emotional profile, and health) ( p < 0.05) than the private group.…”
mentioning
confidence: 99%